DASAR-DASAR AJARAN ISLAM, AL- QUR’AN DAN KESETARAAN GENDER - Iksan; M Pratama, Predi (CV RIFAINSTITUT, 2021)
This article aims to explain and analyze the relationship between Islam and gender, while the research method used is literature study, namely a series of activities related to methods of collecting library data, reading and taking notes and processing research materials. Meanwhile, the data sources in this study were obtained from books, articles, journals and the internet. The data sources are divided into two categories, namely primary and secondary data sources. Primary data sources, namely books and previous research, then secondary data sources consisting of journals, articles, magazines, literature, documents, and so on. The two kinds of research sources are then used as the author's research material to be analyzed in order to find answers to the problems that are the focus of the research. Meanwhile, the main findings in this study are the general view of gender, the Islamic view of gender, justice in Islam, the concept of gender bias in the Koran, gender equality in the perspective of the Koran and the principle of equality. The principle of gender equality in an Islamic perspective is that men and women are the same in several ways, namely; as a servant of Allah, as the caliph of Allah, accepted the primordial covenant, was actively involved in the events of the cosmic drama, and had the same potential for achievement. This principle is clearly outlined in the Islamic teaching guidelines in the form of texts or texts from the Qur'an and Hadith. Meanwhile, the difference between men and women can only be seen in terms of the level of devotion to Allah SWT.